2018
DOI: 10.1007/s40629-018-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-celiac gluten/wheat sensitivity (NCGS)—a currently undefined disorder without validated diagnostic criteria and of unknown prevalence

Abstract: Within the last decade, non-celiac gluten/wheat sensitivity (NCGS) has been increasingly discussed not only in the media but also among medical specialties. The existence and the possible triggers of NCGS are controversial. Three international expert meetings which proposed recommendations for NCGS were not independently organized and only partially transparent regarding potential conflicts of interest of the participants. The present position statement reflects the following aspects about NCGS from an allergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…Over the years, the number of studies on this topic and the number of patients diagnosed with NCGS has significantly increased. It is difficult to access the exact prevalence of NCGS since we still do not have validated biomarkers for the diagnosis of NCGS [2,7,8,9]. However, previous studies have reported a prevalence rate of NCGS between 0.5 and 13% [1,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the number of studies on this topic and the number of patients diagnosed with NCGS has significantly increased. It is difficult to access the exact prevalence of NCGS since we still do not have validated biomarkers for the diagnosis of NCGS [2,7,8,9]. However, previous studies have reported a prevalence rate of NCGS between 0.5 and 13% [1,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NCWS has been documented to range between 0.6 to 13% in the general population. However, because of the lack of diagnostic criteria, biomarkers, and misconceptions on self-diagnosis, the actual prevalence of NCWS cannot be established with a level of confidence today [70]. These epidemiological studies have suggested that gluten-associated disorders are common around the globe, and reflected toward a need for the "gluten-free" products.…”
Section: Celiac Disease Prevalencementioning
confidence: 99%
“…Es ist daher nachvollziehbar, das der langfristige Einsatz von Low-FODMAP-Diäten mit hohem Proteinanteil zumindest problematisch ist [68], solange Langzeitstudien fehlen [69]. Im klinischen Alltag wird empfohlen, sukzessive FODMAPs wieder zuzuführen und die Symptomentwicklung zu beobachten, vergleichbar der Strategie bei einer anderen fragwürdigen Therapie, der glutenfreien Ernährung in der Nicht-Zöliakie-Population [70]. In den vergangenen 15 Jahren (bis 2015) wurden mehr als zehn Metaanalysen und systematische Übersichtsarbeiten zur Wirksamkeit von Probiotika veröffentlicht [72 -79], aber keine war in der Lage, zu einem eindeutigen Fazit zu kommen; ebenso weitere Metaanalysen von 2018 und 2019 [71].…”
Section: Modifizierung Der Darmmikrobiotaunclassified